Sikap petani terhadap adopsi inovasi sistem tanam jajar legowo - Simatupang, Donny Ivan Samuel; Pakpahan, H.T.; Nazara, D.C.B. (Universitas Muhammadiyah Mataram, 2022)
The jajar legowo planting system needs to be implemented in all regencies/cities in North Sumatra, because this planting system is an attempt to optimized agricultural yields. This study purposes were: 1) determined the farmers’ attitude to implement the jajar legowo system; 2) determined the factors that influence the implementation of jajar legowo system at the research site; and 3) determined how farmers implemented the jajar legowo planting system at the research site. The method used to determine the research location applies purposive sampling. The method of determining the sample used is